Vegetable oils and oilseeds - Great Britain; Commonwealth Economic Committee; Commonwealth Secretariat (London : Her majesty's stationery office, 1967)
This review is published annually by the Committee with the aim of presenting in convenient form up-to-date summaries of production, international trade and consumption for a group of allied commodities, with special reference to the part played by the countries of the Commonwealth.
A review of production, trade, utilization and prices relating to groundnuts, cottonseed, linseed, soya beans, coconut and oil palm products, olive oil and other oilseeds and oils.
Includes bibliographical footnotes
hza 01/02/2019
Loans
Keywords: Oil industries; Vegetable oils; Commonwealth countries; Great Britain